The Relationship Between Education and Family Support with Elderly Visits in Patients with Diabetes Mellitus in the Elderly Posyandu of the Puskesmas Working Area Bumidaya District Hospitalization South Lampung - Ari Kurniawan; Tri Adi Nugroho; Rizki Yeni Wulandari; Riska Hediya Putri (Sean Institute, 2025)
The International Diabetes Federation (IDF) in 2021 recorded 19.47 million people with diabetes mellitus in Indonesia with a prevalence of 10.6% and is predicted to increase to 28.57 million in 2045. The number of elderly people with diabetes at the Bumidaya Health Center has increased from 2022, namely 125 people to 146 people 2023. The risk factor for most diabetics is the elderly, one of the government's efforts to improve the health of the with the elderly Posyandu program, but the activity rate of the elderly visit to the Bumidaya Puskesmas is still low, which is below 50%, which means that this figure is still below the Ministry of Health standard with a minimum of 8 attendances or 66% in one year. Education and family support are needed to improve the quality of life of the elderly. The purpose of the study was to determine the relationship between education and family support with visiting elderly diabetes mellitus at the Bumidaya Health Center. Type of quantitative research using cross sectional method. The study population was elderly with a history of diabetes mellitus. The number of research samples was 102 respondents taken by purposive sampling technique. Research time October 10-24, 2024. Collecting data on education and family support using a questionnaire, data on the activity of elderly visits with the elderly Posyandu register book. Bivariate analysis using Chi square and Mann whitney tests. Based on statistical tests obtained p-value 0.539> α (0.05) there is no relationship between education and elderly visits and p-value 0.025 < α (0.05) there is a relationship between family support and elderly visits. It is hoped that health workers will improve health services, the elderly family always provides support by accompanying and motivating the elderly to maintain health and routinely come to the Elderly Posyandu.